2013
DOI: 10.5194/hess-17-2781-2013
|View full text |Cite
|
Sign up to set email alerts
|

On the sources of global land surface hydrologic predictability

Abstract: Abstract. Global seasonal hydrologic prediction is crucial to mitigating the impacts of droughts and floods, especially in the developing world. Hydrologic predictability at seasonal lead times (i.e., 1-6 months) comes from knowledge of initial hydrologic conditions (IHCs) and seasonal climate forecast skill (FS). In this study we quantify the contributions of two primary components of IHCs -soil moisture and snow water content -and FS (of precipitation and temperature) to seasonal hydrologic predictability gl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(89 citation statements)
references
References 60 publications
5
83
1
Order By: Relevance
“…The probability of drought onset detection is higher over parts of North America, Europe, West Russia, and East Africa (Figure 1a). An interesting feature is that areas with relatively higher drought detectability are not located over either humid or arid regions in terms of annual mean precipitation, suggesting that the initial condition for drought onset forecast is more important in transition zones, a finding consistent with Shukla et al [2013]. On average, globally, the drought detectability of the ESP approach is about 0.16 (Table 1).…”
Section: Resultssupporting
confidence: 72%
“…The probability of drought onset detection is higher over parts of North America, Europe, West Russia, and East Africa (Figure 1a). An interesting feature is that areas with relatively higher drought detectability are not located over either humid or arid regions in terms of annual mean precipitation, suggesting that the initial condition for drought onset forecast is more important in transition zones, a finding consistent with Shukla et al [2013]. On average, globally, the drought detectability of the ESP approach is about 0.16 (Table 1).…”
Section: Resultssupporting
confidence: 72%
“…Yossef et al (2013) showed that in western Europe, from July to October, streamflow forecasts are more dependent on meteorolog-ical forcing than they are on initial conditions, even 1 month ahead. The conclusions of Shukla et al (2013) are quite consistent with these findings. They found that the predictability of a forecast issued in July in France lies in the meteorological forcing for horizons longer than 3 months.…”
Section: Approaches To Seasonal Streamflow Forecastingsupporting
confidence: 82%
“…Research has shown that the relative role of each source of predictability mainly depends on the "inertia" or "memory" of the studied basin, the forecast season and the forecast lead time (Wood and Lettenmaier, 2008;Shukla et al, 2013;Yossef et al, 2013;Wood et al, 2016). Yossef et al (2013) showed that in western Europe, from July to October, streamflow forecasts are more dependent on meteorolog-ical forcing than they are on initial conditions, even 1 month ahead.…”
Section: Approaches To Seasonal Streamflow Forecastingmentioning
confidence: 99%
“…We use this term to emphasize the difference of "forecastability" from "predictability", the latter being an objective physical feature of the hydrological system and does not depend on the forecasting methodology (see e.g. Report…, 2002;Shukla et al, 2013). 25 Forecastability maps of four inflow characteristics are shown in Fig.…”
Section: Influence Of the Forecast Issue Date On The Forecast Performmentioning
confidence: 99%